TALENT MANAGEMENT DISCLOSURE AS A MEDIATOR BETWEEN CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE (Malaysian Management Journal, 2022)
Active participation from the corporate sector in designing and implementing corporate social responsibility (CSR) activities is critical for company resilience and reliance. It has been suggested that companies need to integrate CSR activities with talent management strategies. However, the extant literature on CSR reporting has limited research focusing on talent management in CSR activities. Therefore, this study examines the extent of talent management disclosure (TMD) made by the top 100 Malaysian public-listed companies (PLCs). Particularly, this study examines the mediating effect of TMD on the corporate governance characteristics (CGC) and corporate financial performance (CFP) relationship. Generalised Linear Modelling (GLM) was used to analyse the cross-sectional data. The results indicate that female directors positively influence CFP, whereas independent directors negatively correlate with CFP. This study also finds that TMD has an insignificant moderating role in the CGC and CFP relationship. Nevertheless, the newly developed TMD provides a new perspective on talent management research. TMD is a new research avenue under-researched and needs more academic and business executive attention. Thus, this research invites academia and company management to revisit CSR activities by embedding talent management strategies.